PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA AYAM GEPREK WENING GONDANGREJO, KARANGANYAR - Aryani, Selvi; Ambarwati, Della Putri; Ilham, Muhammad Dzaky; Rahadhini, MD (Jurnal Bina Bangsa Ekonomika, 2025)
With the increasingly fierce competition in the culinary business, service quality is an important factor that can affect customer loyalty. Customer satisfaction acts as a mediating variable that strengthens the relationship between service quality and customer loyalty. The purpose of this study is to find out and analyze the influence of service quality on customer loyalty with customer satisfaction as a mediating variable in Ayam Geprek Wening Gondangrejo, Karanganyar. This study uses a survey method with a quantitative research approach and primary data sources. The data analysis techniques used include Hierarchical Regression Analysis and Path Analysis, as well as Hypothesis Testing using Significance Tests (t-Test and F-Test). The results of the study show that there is a significant influence between service quality and customer loyalty, both directly and through customer satisfaction as a mediating variable. Good service quality can increase customer satisfaction, which in turn increases customer loyalty to Ayam Geprek Wening. The implementation of high service quality at Ayam Geprek Wening Gondangrejo, Karanganyar has been done well, but continuous efforts are still needed to improve service aspects so that customer satisfaction and loyalty continue to increase. This can be done by providing periodic training to employees to maintain service standards and add innovative menu variations to keep customers interested